المبارزة الأدبية والإرث: البصمة الثقافية لعلقمة بن عبده الفحل: LITERARY DUEL AND LEGACY: THE CULTURAL IMPRINT OF ʿALQAMAH IBN ʿABADAH - Dr Hafiz Ahmed Saeed Rana; Muhammad Sohail, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
This article explores the literary and historical aspects of the life and works of ʿAlqamah Ibn ʿAbadah, a pre-Islamic poet renowned for his eloquence and intricate depictions of Arabian life, particularly his portrayal of horses and the desert environment. ʿAlqamah, a member of the Banū Tamīm tribe, is often associated with the ʿUḏrī romantic tradition, and his poetry serves as a significant cultural artifact from the Jāhiliyyah period. The narrative delves into a famous poetic duel between ʿAlqamah and ʿAmr Ibn Kulthūm, showcasing their poetic prowess and the societal esteem held for eloquent speech in Arab tribal culture. This incident highlights the importance of poetry as a means of social commentary and moral reflection, illustrating the poet's role as an observer and critic of cultural norms. Further, the article discusses various historical accounts and interpretations of ʿAlqamah's life, including his interactions with other poets and tribal leaders, which paint a vivid picture of the socio-political landscape of pre-Islamic Arabia. It also addresses scholarly debates over the authenticity and meanings of certain poetic verses attributed to him, reflecting on the complexities of oral transmission and historical documentation in early Arabic literature. The article also examines the thematic elements of heroism, generosity, and tribal allegiance in ʿAlqamah's poetry, which are emblematic of the values admired in his society. These themes not only underscore the poet's literary genius but also provide insights into the ethos that characterized the tribal dynamics of his time. In conclusion, the piece affirms ʿAlqamah's contribution to Arabic literature, positioning him as a pivotal figure in the cultural heritage of Arabia, whose works continue to be studied for their artistic merit and historical value.